2020
DOI: 10.1186/s12872-020-01562-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis evaluation of universal acute coronary syndrome: the interplay between SYNTAX score and ApoB/ApoA1

Abstract: Background: Acute coronary syndrome (ACS) is a group of clinical syndromes associated with substantial morbidity and mortality rate. SYNTAX and SYNTAX II score used to be a reference for surgical selection of coronary revascularization and prognosis evaluation in patients with 3-vessel or left main artery disease. In addition, apoB/ apoA1 is an important predictor of ACS risk. This study aims to assess the prognosis value of different kinds of SYNT AX score together with apoB/apoA1 in universal ACS patients (R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Estimated Apo-B is thought to be associated with hs-CRP, microalbuminuria, Agatston calcium score 33 as well as SYNTAX score. 20 Furthermore, a robust correlation was found between Apo-B reduction and regression of atherosclerotic plaques (coronary plaque volume). 34 Accordingly, Apo-B serves as a useful biomarker providing incremental risk assessment through linking with multiple potential risk indicators.…”
Section: Endpointsmentioning
confidence: 92%
See 1 more Smart Citation
“…Estimated Apo-B is thought to be associated with hs-CRP, microalbuminuria, Agatston calcium score 33 as well as SYNTAX score. 20 Furthermore, a robust correlation was found between Apo-B reduction and regression of atherosclerotic plaques (coronary plaque volume). 34 Accordingly, Apo-B serves as a useful biomarker providing incremental risk assessment through linking with multiple potential risk indicators.…”
Section: Endpointsmentioning
confidence: 92%
“…On the other hand, there are more studies almost in concordance with our findings. [7][8][9][15][16][17][18][19][20] These studies are very heterogeneous due to different clinical contexts, population enrolled, timing of lipoprotein assays, and underlying treatment options. Most of these researches have been performed among low-risk individuals or patients with stable ischemic heart disease (SIHD) while our study is confined to STEMI.…”
Section: Endpointsmentioning
confidence: 99%
“…2 However, numerous in vivo human cohort studies have suggested that another factor in CHD risk might be the apolipoprotein B100/ apolipoprotein AI (ApoB100/ApoAI) ratio. [3][4][5][6][7] ApoB100 is a large surface protein present on low-density lipoprotein (LDL) and serves as a ligand for the LDL receptor, which facilitates its clearance from the plasma. Apolipoprotein AI (ApoAI) is the major protein constituent on highdensity lipoprotein (HDL) and plays a central role in reverse cholesterol transport by stabilizing the HDL particle, interacting with the ATP-binding cassette transporter I, activating lecithin cholesterol acyl transferase and acting as a ligand for the hepatic scavenger receptor.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, numerous studies have suggested that another factor in CHD risk might be the apolipoprotein B100/apolipoprotein AI (ApoB100/ ApoAI) ratio. [3][4][5][6][7] ApoB100 is a large surface protein present on low-density lipoprotein (LDL) and serves as a ligand for the LDL receptor, which facilitates its clearance from the plasma. Apolipoprotein AI (ApoAI) is the major protein constituent on high-density lipoprotein (HDL) and plays a central role in reverse cholesterol transport by stabilising the HDL particle, interacting with the ATP-binding cassette transporter I, activating lecithin cholesterol acyl transferase and acting as a ligand for the hepatic scavenger receptor.…”
Section: Introductionmentioning
confidence: 99%